Coxiella burnetii infection with women's febrile spontaneous abortion reported in Algiers. (November 2018) - Ghaoui, H.; Bitam, I.; Ait-Oudhia, K.; Achour, N.; Saad-Djaballah, A.; Saadnia, F.Z.; Kedjour, S.; Fournier, P.-E.
Abstract: We investigated Q fever infection in Febrile Spontaneous Abortions in women by using a serologic method (Immuno-Fluorescence Assay, IFA) and a molecular method (real-time quantitative PCR, qPCR) in Obstetric-Gynaecology (OB-GYN) services in two hospitals in Algiers. We included in the case group 380 women who experienced Febrile Spontaneous Abortion; the control group comprised 345 women who gave birth without any other infections or complications. Among the 725 women included, antibodies against Coxiella burnetii were detected by IFA in three (03) cases patients; all control group samples were IFA negative. In other hand, only four (04) placental samples among the case group came back with q PCR positive for IS1111 and IS30a too. A relationship between C. burnetii infection and febrile spontaneous abortion exists in OB-GYN services in Algiers.